Challenges in the social environment landscape: readiness of youth in embracing diversity - Md. Yassin, Sulaiman; Dahalan, Dzuhailmi; Abdullah, Haslinda; Ismail, Ismi Arif; Hamzah, Azimi; Ahmad, Nobaya; Idris, Fazilah; Yee, Wendy Mei Tien; Serit, Banyan (Universiti Putra Malaysia Press, 2013)

(untitled)
This article discusses the readiness of youth of various races in Malaysia to celebrate diversity in the daily social landscape of society. Youth are at the forefront in facing the challenges of addressing diversity in a multicultural community. The readiness of youth to face diversity is measured using questionnaires. This study involves a total of 600 respondents from secondary schools and higher education institutions. The results showed that generally, the level of respondents’ readiness to accept diversity was high. There were significant differences found in terms of gender, ethnicity and residential locations in which the respondents had their upbringing. The findings were consistent with findings from earlier studies.